2011
DOI: 10.1136/flgastro-2011-100011
|View full text |Cite
|
Sign up to set email alerts
|

High negative predictive value of a normal faecal calprotectin in patients with symptomatic intestinal disease

Abstract: Background Calprotectin is a heat stable intracellular protein shed by neutrophils into the intestinal lumen in response to infl ammation. Lack of specifi city makes its role in the assessment of infl ammatory bowel disease uncertain. However, the strength of faecal calprotectin testing may lie in its negative predictive value (NPV) rather than positive predictive value (PPV) of organic intestinal disease. Objectives To determine whether a normal faecal calprotectin in new patients with symptoms safely predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…It has now developed an evidence-based care pathway for FC as a triage tool to facilitate the initial clinical assessment of patients presenting with lower gastrointestinal symptoms (Turvill, 2012;2014). The care pathway is designed to optimize the negative and positive predictive values (NPV and PPV) of FC.…”
Section: Introductionmentioning
confidence: 99%
“…It has now developed an evidence-based care pathway for FC as a triage tool to facilitate the initial clinical assessment of patients presenting with lower gastrointestinal symptoms (Turvill, 2012;2014). The care pathway is designed to optimize the negative and positive predictive values (NPV and PPV) of FC.…”
Section: Introductionmentioning
confidence: 99%
“…In a study amongst those with borderline calprotectin levels (> 50 but < 150 g/g), Demir et al (2012) 45 found no significant difference with NSAID use. Conversely, Turvill (2012) 46 reported that 14% of people referred from primary care with intestinal symptoms, and who had raised calprotectin, had a final diagnosis of NSAID enteropathy.…”
Section: Calprotectinmentioning
confidence: 99%
“…14 The NPV of FC for all organic enteric disease was lower than is seen in a younger cohort, because of the increased incidence of noninflammatory enteric disease in the elderly (such as microscopic colitis and pancreatic insufficiency). 4 Diverticulosis in the absence of inflammation was a diagnosis made on occasion by the responsible clinician. Having established its safety, the utility of FC next depends on its PPV.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, should it be sufficiently sensitive, FC might differentiate much organic enteric disease from functional disorders, such as irritable bowel syndrome (IBS). [1][2][3][4] This would empower the expectant treatment of low-risk patients and the cost-effective identification of those requiring urgent investigation.…”
Section: Introductionmentioning
confidence: 99%